Clinical Outcomes of Antihypertensive Therapy in Chronic Kidney Disease: A Literature Review - Candraningrat, I Dewa Agung Ayu Diva; Ayu Sri Handani, Dewa; Vyra Ginanti Putri, Ni Putu; Dirga Mega Buana, Komang (Journal Syifa Sciences and Clinical Research, 2025)
Chronic kidney disease (CKD) carries high cardiovascular risk, and optimal antihypertensive therapy is central to slowing progression. This review synthesized randomized controlled trials from the past 10 years in adults with CKD identified via PubMed, focusing on estimated glomerular filtration rate (eGFR) decline, albumin/protein excretion, and cardiovascular outcomes; study selection followed PRISMA. Renin–angiotensin system inhibitors (RASi) consistently lowered blood pressure, reduced albumin/protein excretion, and attenuated eGFR decline versus comparators. In a crossover trial, azilsartan produced greater reductions in urine protein-to-creatinine ratio and faster blood-pressure control than candesartan. Among calcium channel blockers, benidipine (T/L-type) decreased urinary albumin excretion and improved vascular surrogates versus amlodipine (L-type), suggesting class-specific renal effects. Nifedipine GITS combined with candesartan improved blood-pressure control in high-risk subgroups. Adding spironolactone can further reduce albuminuria but increases hyperkalemia risk; co-administration of patiromer enables RASi/MRA intensification under biochemical monitoring. Overall, RASi remain first-line—particularly in albuminuric CKD—while selected combinations with a dihydropyridine calcium channel blocker or a mineralocorticoid receptor antagonist (with a potassium binder when needed) may augment renoprotection. Treatment should be individualized to CKD stage, comorbidities, and laboratory follow-up.